2009
DOI: 10.1063/1.3263706
|View full text |Cite
|
Sign up to set email alerts
|

Study on the characteristics of turbulent drag-reducing channel flow by particle image velocimetry combining with proper orthogonal decomposition analysis

Abstract: Turbulent drag reduction of 30 ppm cetyltrimethyl ammonium chloride (CTAC) solution flow in a channel was investigated with particle image velocimetry (PIV) combining with proper orthogonal decomposition (POD). Measurements were made at inlet fluid temperature of 304 K and at Reynolds number 2.5×104 (based on the channel height, bulk velocity, and solvent viscosity) for both water and CTAC solution flows with 70.0% drag reduction rate. The two-component velocity fields in the streamwise-wall normal plane were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…It has been previously applied to many experimental and numerical database to characterize the coherent structures present in TBL flows (see for instance Günther and Von Rohr 2003;Gurka et al 2006;Cai et al 2009; Baltzer and Adrian 2011 and references therein). As state above, the present flow configuration is fully unsteady.…”
Section: Expansion Of Pod Methodologymentioning
confidence: 99%
“…It has been previously applied to many experimental and numerical database to characterize the coherent structures present in TBL flows (see for instance Günther and Von Rohr 2003;Gurka et al 2006;Cai et al 2009; Baltzer and Adrian 2011 and references therein). As state above, the present flow configuration is fully unsteady.…”
Section: Expansion Of Pod Methodologymentioning
confidence: 99%
“…White et al [37] studied the turbulence structure in a drag-reduced flat-plate boundary layer flow by means of particle image velocimetry, providing information for further understanding the interaction between the polymer and the near-wall vortex. In addition, various research groups [38][39][40][41][42] performed a series of studies on the turbulent flow with polymer addition and clarified the velocity profile using particle image velocimetry and laser Doppler velocimetry.…”
Section: Mechanism Of Turbulent Drag Reduction With Polymersmentioning
confidence: 99%
“…Cai et al (2009) studied the drag-reducing flow with particle image velocimetry (PIV). They revealed that additives inhibit the turbulent bursting processes and that the contribution of an organized turbulent structure to the turbulent kinetic energy increases.…”
Section: Introductionmentioning
confidence: 99%